Aphasia after Spinal Deformity Correction Surgery in Adolescent Idiopathic Scoliosis A Case Report - Aji Antoro (Journal of Global Pharma Technology, 2019)
AbstractIntroduction. Advancement in operative techniques, better understanding of biomechanics and breakthrough in technology making spinal deformity correction surgery become more feasible and conducted more often. Majority of the neurological complications were related to spinal cord disruption due to technical issues. However, neurological complications that were attributed to a brain pathology, were more likely to be of ischemic origin.Case Illustration. We performed spinal deformity correction surgery on a 20-year old man with adult idiopathic scoliosis classification Lenke 2AN, with Cobb angle of 68°. On the second day, the serum sodium level showed a reduction. MRI examination revealed hyper acute infarct lesion on the posterior lobe of left temporo-parietal aspect. However, DSA examination was unremarkable. On the third postoperative day, his motoric and sensory functions, and sodium level returned to normal state. His cognitive function and communication abilities were able to return to normal gradually.Discussion. Stroke that occurs during spinal deformity correction surgery is reported in 5.8% of operative cases. Prone positioning accompanied by extension of the neck can compress vertebral arteries, causing reduction in vascular flow. Therefore, inappropriate prone positioning on the operating table for a prolonged period may cause cerebral ischemia.Conclusion. This case may serve as a reminder to surgeons and anesthesiologists towards the existence of such complications. Full awareness of the risk, good preoperative assessment, good surgical training, good communication, good teamwork, and good intraoperative and postoperative monitoring will minimize the risk for neurological complications.